The Impact of Environmental Performance on the Cost of Equity Capital: Evidence from Chinese Listed Companies in Heavy Pollution Industries - Zhu, Tiejun (Science, Technology, and Social Sciences Procedia, 2023)
This study aims to explore the evaluation level and evaluation model of environmental performance in China, and further investigate the impact of environmental performance, based on stakeholder theory, information asymmetry theory and the cost of equity capital in the principal-agent industry, as well as previous research. The sample was selected from 1,975 listed companies listed on the Shenzhen Stock Exchange and the Shanghai Stock Exchange from 2018 to 2022. The environmental performance data came from the E-value of ESG score in the Wind database. The PEG model is used to calculate the cost of equity capital of enterprises. It can be found that the environmental performance and equity capital cost of China's heavily polluting industries both show a U-shaped trend of first decreasing and then increasing. From the analysis of environmental performance data, it can be concluded that the current level and mode of environmental performance evaluation in China are still in a relatively early stage. The correlation between variables was tested by regression analysis, and the results showed that there was no significant correlation between environmental performance and equity capital cost in heavily polluting industries, and environmental performance had no significant impact on equity capital cost of enterprises. This study explores the relationship between environmental performance and the cost of equity capital, and puts forward some suggestions to improve environmental performance from different perspectives, and also provides some ideas for future scholars who want to conduct research in this field.